Brazilian Specialists' Perspectives on the Patient Referral Process - Juliani, Carmen [UNESP] (2017)
Since 1988, healthcare has been considered a citizen's right in Brazil. The Sistema Unico de Saude (SUS), has undergone development and expansion to ensure universal health coverage for the Brazilian public, the world's fifth largest population. The coordination of effective communications between primary care physicians, specialists and patients is a significant challenge, particularly the referral process. Our study objective was to understand the facilitators and barriers associated with referral process communications between primary care physicians and regional university hospital specialists in the State of Sao Paulo. This paper reports specialists' perspectives of the referral process. This was a phenomenological study that employed a qualitative research method with three components (description, reduction and comprehension). We conducted focus groups with 54 hospital residents from different specialties (surgery, medicine, obstetrics/gynecology, pediatrics) from July to October 2014. The main results showed lack of an adequate referral-return referral process resulting in treatment delays and inappropriate use of emergency services. Communications were impeded by lack of integrated, computerized booking and standardized referral-return referral processes; underlying lack of trust in primary care physicians; and patients' inappropriate use of healthcare services. Although computerized systems will facilitate communications between primary and specialty care, other strategies are needed to promote collaboration between services, and ensure appropriate utilization of them.